PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL BERBASIS CANVA PADA MATA PILIHAN PUBLIC SPEAKING KELAS XI MP SMK NEGERI 8 JAKARTA - Nurhalidza Rahayu, Siti; Faslah, Roni; Riyantie, Mayang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by learning problems in Public Speaking at SMK Negeri 8 Jakarta, where 57.1% of students considered conventional text-based learning media boring and 71.4% struggled to understand practical material due to limited concrete visual examples. This study aims to: (1) describe the development process of a Canva-based E-Module learning media for the Public Speaking elective subject in Class XI MP at SMK Negeri 8 Jakarta; (2) evaluate the validity of the E-Module based on assessments from material, media, and instructional design experts; and (3) test its practicality based on student responses. This study utilized the Research and Development (R&D) method with the ADDIE development model, consisting of five stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects included expert validators and Class XI MP students of SMK Negeri 8 Jakarta in small group and field trials. Data were collected through pre-research needs assessment questionnaires, expert validation sheets, and student practicality questionnaires, which were then analyzed using descriptive quantitative and qualitative techniques. The results indicated that the media achieved validation scores of 98.33% from the material expert, 91.67% from the media expert, and 88.33% from the instructional design expert, yielding an average of 92.78% in the "Very Valid" category. The practicality test scored 95.71% in small group trials and 96.85% in field trials, averaging 96.28% in the "Very Practical" category. Consequently, the Canva-based E-Module meets the validity and practicality criteria, making it suitable for Public Speaking instruction.